2022
DOI: 10.1177/08968608221130559
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of PD for AKI treatment during COVID-19 in New York City: A multicenter study

Abstract: Background: The high incidence of acute kidney injury (AKI) requiring dialysis associated with COVID-19 led to the use of peritoneal dialysis (PD) for the treatment of AKI. This study aims to compare in-hospital all-cause mortality and kidney recovery between patients with AKI who received acute PD versus extracorporeal dialysis (intermittent haemodialysis and continuous kidney replacement therapy). Methods: In a retrospective observational study of 259 patients with AKI requiring dialysis during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This observation was supported by the more recent reports of acute PD during the COVID-19 pandemic from New York and the UK, where 30-100% of patients were on mechanical ventilators [24,26,28,37]. Bowes et al reported that in 36 mechanically ventilated patients on PD, the Sequential Organ Failure Assessment (SOFA) score and the arterial oxygen partial pressure to fractional inspired oxygen concentration ratio (PaO 2 :FiO 2 ) remained unchanged 24 h after initiating PD.…”
Section: Is Pd Unsuitable For Mechanically Ventilated Patients?mentioning
confidence: 75%
See 1 more Smart Citation
“…This observation was supported by the more recent reports of acute PD during the COVID-19 pandemic from New York and the UK, where 30-100% of patients were on mechanical ventilators [24,26,28,37]. Bowes et al reported that in 36 mechanically ventilated patients on PD, the Sequential Organ Failure Assessment (SOFA) score and the arterial oxygen partial pressure to fractional inspired oxygen concentration ratio (PaO 2 :FiO 2 ) remained unchanged 24 h after initiating PD.…”
Section: Is Pd Unsuitable For Mechanically Ventilated Patients?mentioning
confidence: 75%
“…Fully adjusted Cox regression analysis showed that the PD group had a significantly lower mortality risk (hazard ratio of 0.48; confidence interval 0.27–0.82; p 0.008). There was no difference in renal function recovery at 30 days between both groups [24].…”
Section: Introductionmentioning
confidence: 99%
“…A study with 12-month follow-up reported that mortality in COVID-19 patients with renal involvement is higher even with hemodialysis compared to patients with hemodialysis but without COVID-19 infection [48]. An observational study from New York reported that compared to extracorporeal dialysis, the treatment of AKI with peritoneal dialysis was not associated with worse clinical outcomes [49]. Another study reported that mortality was higher in patients with hemodialysis compared to peritoneal dialysis and renal transplant patients, while mortality was higher in peritoneal dialysis and renal transplant patients compared to the general population.…”
Section: Management and Treatment Of Akimentioning
confidence: 99%
“…In adults, the most common underlying factors leading to AKI requiring KRT included cardiovascular diseases, infectious diseases, renal diseases, respiratory diseases, and gastrointestinal diseases [35,41,42,77,78]. In addition, comorbidities in adult patients comprised diabetes mellitus, coronary artery disease, hypertension, CKD, heart failure, and liver cirrhosis [41,78].…”
Section: Underlying Comorbidities In Akimentioning
confidence: 99%
“…According to various studies, the percentage of patients who recovered kidney function ranged from 9.3% to 60.3%, while 4.3% to 38.7% progressed to CKD, and 30.2-72% of patients died [34][35][36][37]39,41,77,78]. Randomized control trials or multicenter studies reported better outcomes [35,77].…”
Section: Outcomes Of Uspd In Children With Akimentioning
confidence: 99%